Невеста по наследству: [роман] / Ирина Мельникова - Мельникова Ирина Александровна (Вера, надежда, любовь, 2008)
Экземпляры: ф. 4 (20081201) / Инвентарный номер: 93075 / Цена: 39.50 / Авт.знак: М 48 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6